(untitled) (Sebha University Conference Proceedings, 2024)
Algeria seeks to achieve great progress in the field of digitization, and has reached advanced levels in many sectors in terms of generalizing digital services and developing a secure database, to bring the administration closer to the citizen and ensure the quality of services. The study assumed the existence of a statistically significant relationship between digital transformation and the vocational training sector in Algeria The study used the descriptive analytical approach, and the study population consisted of directors of vocational training institutes and centers Heads of departments, educational advisors, and vocational training professors. The study used a random sample, and (110) questionnaires were distributed via the Statistical Package for the Social Sciences (SPSS) program. The study reached several results, including: There is a statistically significant relationship between digital transformation and the organization of the vocational training sector in Algeria, as digital transformation has made the vocational training sector rise to the degree of modernity through the use of technology in providing services. . Digital transformation has made translation of regulatory information easy to understand and confusion-free. complication. Digital transformation contributed to the neutrality of training data and raised the quality of services provided to citizens. The study recommended increasing attention to digital transformation in covering all training services electronically. It also recommended increasing attention to training, improving the level and qualifying human cadres to keep pace with rapid technological developments.